The future is Asian : - Khanna, Parag (Simon & Schuster, 2019)
The “Asian Century” is even bigger than you think. Far greater than just China, the new Asian system taking shape is a multicivilizational order spanning Saudi Arabia to Japan, Russia to Australia, Turkey to Indonesia - linking five billion people through trade, finance, infrastructure, and diplomatic networks that together represent 40 percent of global GDP. China has taken a lead in building the new Silk Roads across Asia, but it will not lead it alone. Rather, Asia is rapidly returning to the centuries-old patterns of commerce, conflict, and cultural exchange that thrived long before European colonialism and American dominance. Asians will determine their own future - and as they collectively assert their interests around the world, they will determine ours as well.